An efficient strategy for heterologous expression and purification of active peptide hainantoxin-IV. - Hui Zhang; Peng-Fei Huang; Er Meng; Wen-Ying Li; Lu Zhou; Ling-Yun Zhu; Lei Wu; Meng-Jie Li; Song-Ping Liang; Dong-Yi Zhang (PLoS ONE)
Hainantoxin-IV (HNTX-IV) from the venom of the spider Selenocosmia hainana is a potent antagonist that specifically inhibits the tetrodotoxin-sensitive (TTX-S) sodium channels. The toxin peptide consists of 35 amino acids and adopts a typical inhibitory cystine knot (ICK) motif. To obtain adequate HNTX-IV peptides for further insight into the structure-activity relationships of the toxin, a novel strategy including cloning, expression and purification was developed in an E. coli expression system. For this purpose, a seamless restriction-free (RF) cloning method was employed for the construction of an expression vector to avoid introducing unwanted sequences into the target gene. Furthermore, the solubility of recombinant HNTX-IV could be promoted efficiently by the combination of a glutathione S-transferase (GST) tag and a small ubiquitin-related modifier (SUMO) tag. Finally, an affinity-chromatography-free purification strategy was developed by cut-off dialysis tubing combined with trichloroacetic acid (TCA) extraction. Further HPLC purification yielded recombinant, tag-free HNTX-IV with high yield and purity. The molecular weight of recombinant HNTX-IV (rHNTX-IV) is identical to its theoretical value according to Matrix-Assisted Laser Desorption / Ionization Time of Flight Mass Spectrometry (MALDI-TOF-MS) analysis. The recombinant toxin has similar activity (IC50 value of 120 nM) on the tetrodotoxin-sensitive (TTX-S) sodium channels in adult rat dorsal root ganglion (DRG) neurons to native toxins. In the report, an efficient and cost-effective strategy for producing rHNTX-IV was developed, which paved the way for the further study of structure-activity relationships of rHNTX-IV and its pharmaceutical applications.